Analisis Putusan Majelis Hakim Dalam Perkara Perbuatan Melawan Hukum Bersekongkol Dan Bersama-Sama Telah Berbuat Curang Pada Surat Perjanjian / Akad Kredit - Tami Rusli; Daffa Kresna Gading (Universitas Sang Bumi Ruwa Jurai, 2023)
The definition of credit is expressly stated in the provisions of Article 1 number 11 of Law Number 7 of 1992 as amended by Law Number 10 of 1998 (hereinafter referred to as the Banking Law) which states that credit is the provision of money or bills that can be equated with it, based on an agreement or loan agreement between a bank and another party that requires the borrower to pay off the debt after a period of time with interest. The research problem is what is the responsibility for the unlawful act of conspiring and together having cheated on the letter of agreement/credit contract Tanjung Karang District Court Decision Number: 164/Pdt.G/2021/PN Tjk?, what is the judge's consideration in deciding the action lawsuit case? against the law conspiring and together cheating on the letter of agreement / credit agreement in the Tanjung Karang District Court Decision Number: 164/Pdt.G/2021/PN Tjk. The research method used is a normative and empirical approach using secondary and primary data, data obtained from field studies, literature studies, and then carried out qualitative juridical analysis. Based on the research results, the responsibility for the unlawful act of conspiring and together having cheated on the letter of agreement/credit contract in the Tanjung Karang District Court Decision Number: 164/Pdt.G/2021/PN Tjk is to declare it null and void (Nietig) or at least the Letter of Agreement/Credit Agreement No.260/XII/2018 dated 13-12-2018 and the issuance of the Mortgage Ownership Certificate between Defendant I are declared void, punishing Defendant I through Defendant V jointly and severally to pay (Dwangsom) or forced money to the Plaintiff in the amount of Rp. 100,000,- (One hundred thousand rupiah) per day, ordered Defendant V to cancel An's Mortgage Ownership Certificate. The plaintiff and charged the costs incurred in this case to Defendant I to Defendant V in the amount of Rp. 4,710,000.00,- (four million seven hundred and ten thousand rupiah) and the judge's consideration in deciding the case of the lawsuit against the unlawful act of conspiring and jointly committing cheating on the letter of agreement / credit agreement in the Tanjung Karang District Court Decision Number: 164/Pdt.G/2021/PN Tjk is that there was a mismatch between the documentary evidence and the Plaintiff's witnesses so that the Panel of Judges concluded that Defendant I had used / pledged the ownership certificate Number 13965/KD in the name of the Plaintiff which explains that the Plaintiff's inherited assets are certainly not the rights of Defendant I guaranteed in the financing agreement Number 260 dated 13 December 2018 with Defendant III. This is an act that is contrary to the law or statutory regulations and can be said to be an unlawful act.